Development of the Acid-Base Microblogs Based on Malay Ethnochemistry to Preserve Culture - Utin Dian Anggreni; Dini Hadiarti; Raudhatul Fadhilah (Jurnal Penelitian Pendidikan IPA, 2023)
Perceiving culture in the globalization era is challenge for the Malay community. The best way to solve it is to integrate ethnochemistry into chemistry learning at the school. The research aims to develop acid-base microblogs based on the ethnochemistry of the Malay community. Three Stages Research and Development (TSRD) model was conducted in this study which consists of 3 steps: planning, development, and dissemination. The subjects of this research were the students of XI MIPA class at SMAN 11 Pontianak, SMA Muhammadiyah 1 Pontianak, and MAN 3 Pontianak. The validity assessment and response sheet were used to collect data in this study. The results of the acid-base microblogs based on the ethnochemistry of Malay culture obtained 0.85 of validity from the expert judgment in the very high category. An excellent response was given by the student to the microblog, with a percentage of 82.28%. Based on the study results, the ethnochemistry microblogs have been declared very valid to arouse preserving culture.